Faktor-Faktor Yang Mempengaruhi Minat Masyarakat Kisaran Kota Menggunakan Produk Bank Syariah Indonesia - Syahputra, Danil (Yayasan Rahmat Islamiyah, 2025)
This research aims to test the variables of Service, Knowledge and Trust on interest in using Indonesian Sharia Bank products. This research was conducted in Kisaran City, Asahan Regency. The research approach used is quantitative, and what can be obtained comes from distributing questionnaires to research respondents. The tool used in data processing uses Smart PLS. The results obtained show that there is an influence of the Knowledge and Trust variables on the interest of the people of Kisaran City in using Bank Syariah Indonesia products.